2013
DOI: 10.1149/04701.0195ecst
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hybrid Sol-Gel Coatings Doped with Hydrotalcite-likeCompounds on Steel and Stainless Steel Alloys

Abstract: Hybrid sol-gel organic-inorganic coatings have been extensively studied to their active properties to protect different metal surfaces. Incorporation of non-hydrolysable groups in conjunction with different molar ratio of sol-gel precursors dissolved in distinct solvents lead to an increment of better protective barrier properties. Different hybrid silica sol-gel coatings were prepared changing the type and content of solvent (2-propanol, ethylacetate, ethanol). Coatings were deposited by dip-coating method on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The advantages and disadvantages of these materials, and the processing methods developed were discussed. Table 2 shows that numerous OIH sol-gel coatings for corrosion applications were developed [30,50,137,[191][192][193][194][195][196][197]. The number of reviews reported, only since 2016, clearly indicates that this field is still under development and is far from reach a matured stage.…”
Section: [138]mentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages and disadvantages of these materials, and the processing methods developed were discussed. Table 2 shows that numerous OIH sol-gel coatings for corrosion applications were developed [30,50,137,[191][192][193][194][195][196][197]. The number of reviews reported, only since 2016, clearly indicates that this field is still under development and is far from reach a matured stage.…”
Section: [138]mentioning
confidence: 99%
“…The number of reviews reported, only since 2016, clearly indicates that this field is still under development and is far from reach a matured stage. Several OIHs for corrosion mitigation have been proposed for a wide range of metallic substrates, including aluminum and its alloys [30,63,74,137,198], carbon steel [193], stainless steel [196,[199][200][201] and galvanized steel [16,17,[202][203][204]. Copper [205][206][207] and magnesium [208][209][210][211][212][213][214] based alloys are other types of substrates in which OIH sol-gel coatings were used.…”
Section: [138]mentioning
confidence: 99%
“…Moreover, the treatment of sol–gel hybrid coatings by doping with environmentally friendly inhibitory materials is a promising approach that prevents the corrosion of the substrate by improving its mechanical properties [ 171 , 172 , 173 ]. The hybrid material used as a coating for corrosion mitigation need to show resistance to the abrasion processes and good adhesion to the substrate surface, including copper [ 174 ], magnesium [ 167 , 175 ] and aluminium based alloys [ 176 , 177 ], stainless [ 178 ], galvanized [ 179 ] and carbon steel [ 180 ]. Generally, the organic–inorganic hybrid compounds, which are featured by covalent bonds between the organic and inorganic components (class II), show properties that are well suited to an anticorrosive product, such as good corrosion protection, good scratch resistance, good corrosion protection, high hydrophobicity and low dielectric constants [ 161 , 181 ].…”
Section: Industrial Coatingsmentioning
confidence: 99%
“…Moreover, the treatment of sol-gel hybrid coatings by doping with environmentally friendly inhibitory materials is a promising approach that prevents the corrosion of the substrate by improving its mechanical properties [167][168] [169]. The hybrid material used as a coating for corrosion mitigation need to show resistance to the abrasion processes and good adhesion to the substrate surface, including copper [170], magnesium [163][171] and aluminium based alloys [172][173], stainless [174], galvanized [175] and carbon steel [176].…”
Section: Industrial Coatingsmentioning
confidence: 99%